Academic motherhood - what happens when you can't make it happen? - Kamerlin, Shina Caroline Lynn ; 0000-0002-3190-1173 (EMBO Reports, 2021)
We need more openness about age-related infertility as it is a particular risk for many female scientists in academia who feel that they have to delay having children.
© 2021 The Author.
Keywords: Child; Communication; Female; Humans; Infertility, Female